2017
DOI: 10.3934/ipi.2017022
|View full text |Cite
|
Sign up to set email alerts
|

Ambient noise correlation-based imaging with moving sensors

Abstract: Waves can be used to probe and image an unknown medium. Passive imaging uses ambient noise sources to illuminate the medium. This paper considers passive imaging with moving sensors. The motivation is to generate large synthetic apertures, which should result in enhanced resolution. However Doppler effects and lack of reciprocity significantly affect the imaging process. This paper discusses the consequences in terms of resolution and it shows how to design appropriate imaging functions depending on the sensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…When the observer is moving, the autocorrelation function of the recorded signal depends in a complicated and interesting way of the environment. In [10] the situation in which a receiver is moving along a circular trajectory is addressed. It is shown that the autocorrelation function of the recorded signal is related to the matrix of Green's function between pairs of points along the trajectory, more exactly to a diagonal band of this matrix whose thickness is determined by the velocity of the receiver.…”
Section: Introductionmentioning
confidence: 99%
“…When the observer is moving, the autocorrelation function of the recorded signal depends in a complicated and interesting way of the environment. In [10] the situation in which a receiver is moving along a circular trajectory is addressed. It is shown that the autocorrelation function of the recorded signal is related to the matrix of Green's function between pairs of points along the trajectory, more exactly to a diagonal band of this matrix whose thickness is determined by the velocity of the receiver.…”
Section: Introductionmentioning
confidence: 99%